Impact of Emotional Intelligence and Academic Performance of Tribhuvan university Student of Butwal Sub-Metropolitan City (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to examine the impact of emotional intelligence on academic performance of master running students, studying in Tribhuvan university of Butwal Sub-Metropolitan City.Methods: The study used random sampling technique. A sample size of 253 students of Tribhuvan university of Butwal Sub-metropolitan city. Emotional intelligence was measured using the adapted version of a 30 -items questionnaire featuring a rigorous seven- point Likert scale. Likewise, a descriptive and causal comparative research design was employed, complemented by a comprehensive array of statistical measures, including Mean, Standard Deviation, Correlation, and Regression, independent t test, one-way ANOVA, Mann Whitney U test, F square, and R square, Hypothesis testing and Regression meticulously chosen for robust data analysis.Results: The results reveal that Self-regulation is the major factors for Academic Performance. Likewise, it is also found that motivation, Self-awareness, Empathy are also affect on academic performance.Conclusion: Self-regulation significantly impacts academic performance, as it fosters discipline, time management, focus, and resilience, crucial for effective learning, problem-solving, and goal attainment in educational pursuits.